A intervenção profissional do assistente social na saúde mental dos servidores públicos: um estudo nos tribunais eleitorais do Brasil - ARNAUD, Fernanda Iracema Moura (Universidade Federal do Pará, 2017)
This work is the result of critical reflection and analysis on the professional intervention of the social worker in the mental health of public servants, within its specific practice at Brazilian Electoral Courts, as the situations of mental illness and the risk to health / mental illness the servers mentioned, in those bodies, were evidenced by its frequency and the serious damage caused in the conditions of life and work of them with important consequences also for the institutional mission. Therefore, this study aimed to analyze the professional intervention process Social Worker in these situations, or not caused by work, considering their contributions to the mental health of such servers. It was adopted as a methodological research reference to Marxist theory and its dialectical method, considering the sense of completeness pursued by critical social theory in search of the real movement ownership. It used qualitative research, whose data collection instrument were semi-structured interviews with 21 (twenty-one) subject of three Electoral Courts, involving: health team to belonging professionals (social workers, doctors and psychologists); servers and personnel managers. It is concluded from this study that the mental health of federal public servant is a fraught area tensionalidades which requires, in addition to a clinical approach, a political and social intervention able to respond to numerous contradictions attached to them and give it a grade high complexity, which can not be understood without a substantive reflection on the relationship objectivity-subjectivity, especially on the social determinations, political and economic present at this historic moment marked by deeply destructive capitalist sociability social life, mediated by alienated labor, It reaches people, blocks human development to their full potential of objectification (dehumanization). Thus, it was found in this study that the professional intervention of social workers, albeit limited by structural, cyclical and institutional factors and their relative autonomy, has stated its potential to contribute to the mental health of civil servants of the Electoral Courts , notably with regard to critical reading of institutional and implementing creative strategies for routing demands and identified health needs, embodied the "look at the social" in "social accompaniment", in support to the families, in mediation held between the subjects present in this space (server, management, manager and work team), mobilization and coordination with safety nets and coexistence of individuals in psychological distress, which provides the expansion of rehabilitation resources with a view 'access servers to their social rights. In short, professional answers has favored the improvement of the health status of servers and their families, contributing also to the development of the institutional mission of the Electoral Courts.